(untitled) (London Journal of Medical and Health Research, 2024)
Nonunion of the humeral shaft occurs in between 2% and 10% of non- surgically treated fractures and up to 15% of fractures treated with initial open reduction and internal fixation. The definition of recalcitrant nonunion is still under debate. The purpose of this study is to present the outcomes of a series of patients with recalcitrant pseudarthrosis of the humerus who were treated with stable osteosynthesis combined with biological reconstruction using allograft utilizing a novel surgical approach.